Outcomes After Laparoscopic Enucleation of Pancreatic Neoplasms at a Single High Volume Italian Institution - Daskalaki, Despoina; Marchegiani, Giovanni; Damoli, Isacco; Malleo, Giuseppe; Bassi, Claudio; Butturini, Giovanni (JOP. Journal of the Pancreas, 2012)
Context Pancreatic enucleation is the best procedure for removing small, benign, solid pancreatic tumors but it can increase the post-operative morbidity. Objective The aim of this study was to analyze our results with 10 consecutive laparoscopic enucleations. Methods The analyzed data were retrospectively collected from 10 consecutive patients who underwent laparoscopic enucleation of a pancreatic neoplasm. Results The mean age was 52.5 years (median 46.3 years). The mass was localized at the body-tail of the pancreas in 90% of the patients and at the head in 10%. The mean operative time was 121 minutes. Intraoperative ultrasonography was performed in 6 cases (60%). One patient (10%) developed a grade A fistula. No other post-operative complications occurred. The conversion and mortality rates were both nil. The mean hospital stay was 6.3 days (median 6 days; range 5-8 days). Histologically all 10 specimens were neuroendocrine pancreatic tumors. The median follow-up was 39 months (range 4-74 months) and no patient has presented tumor recurrence or port site hernia. Conclusions Benign tumors of the pancreas can be radically treated with laparoscopic enucleation. It reduces operative time, hospital stay and overall complication rates. This approach should become the gold standard when there is intent to enucleate a small and presumably benign pancreatic tumor.